THE FUNCTIONING FEATURES OF PROOXIDANT-ANTIOXIDANT SYSTEM AND IMMUNE PROTECTION DURING DENTAL CARIES TREATMENT IN CHILDREN WITH NEUROPSYCHIATRIC DISORDERS - O. V. Gulenko; S. B. Khagurova; K. A. Popov (Кубанский научный медицинский вестник, 2018)
Aim. To study the functioning of the prooxidant-antioxidant system and immune defense in the treatment of dental caries in children with psychoneurological disorders in different age groups.Materials and methods. Biological material for the study was oral fluid of patients with tooth decay, with neuropsychiatric disorders (n=84 children) and without comorbid pathology (n=47 children), the control group was 45 people. An evaluation of the severity of the disturbances in the prooxidant-antioxidant system in the oral fluid was carried out by determining the intensity of chemiluminescence in the maximum and the area of the outbreak, as well as the overall antioxidant activity characterizing the state of the antioxidant system. Among the indices of the enzyme link of antioxidant protection, the activity of superoxide dismutase, catalase was determined, and in addition, the integral index of the functioning of antiradical protection enzymes was calculated. Investigation of the state of local immune defense was carried out by determining the content of proinflammatory and pro-inflammatory interleukins, and also assessing the level of lactoferrin. Conclusion. The functioning of the prooxidant-antioxidant system and the regulation of immune defense in children with psychoneurological disorders in different age groups have a number of characteristics with which the clinical indices correlate. The use of complex dental care ("Multistep" regulations) allows more complete rehabilitation of patients and achieving significantly better results in normalizing the biochemical state of the oral fluid.